Mengubah Nilai I'tibārī Di Era Blockchain: Sebuah Penelitian Filosofis Tentang Fenomena Bitcoin - Muhamad Barqi Asila (CV. SINAR HOWUHOWU, 2026)
This article aims to reconstruct the concept of economic value from an Islamic philosophical perspective, taking blockchain technology and Bitcoin as a case study. Departing from the premise that value is i'tibārī that is, arising from collective recognition rather than inherent in substance, this research argues that the shift from gold, fiat currency, to cryptocurrency does not constitute an ontological revolution, but rather a transformation of the institutional medium through which collective recognition is stabilized. Through a synthetic approach combining classical Islamic philosophy and contemporary social constructivism, this study demonstrates that the ontological structure of value remains contingent, while the ethical dimension emerges from the choice of medium, which shapes structures of power and social relations. The analysis reveals that Bitcoin represents not a new metaphysics of value, but a distributed form of i'tibārī value, where recognition is maintained through algorithmic consensus rather than centralized authority. The study concludes that the most ethically preferable medium of value is one that maintains structural stability while minimizing coercive concentration of power, with moral responsibility ultimately resting on the individual. This research contributes to contemporary Islamic philosophy by offering a conceptual framework for understanding digital value without reducing the discourse to normative legal judgments, while providing reflective guidance for Muslim engagement with decentralized economic systems.